Global ammonia (NH3) retrieval from the FY-3F satellite hyperspectral infrared atmospheric sounder and performance assessment - Zhili Deng; Yapeng Wang; Minqiang Zhou; Ling Gao; Lin Chen; Xifeng Cao; Lingfeng Zhang; Yuhan Jiang; Haiyang Dou; Xingying Zhang (Atmospheric Environment, 2026)

Intensive mariculture promotes molecular reorganization of dissolved organic matter in coastal waters - Kai Shen; Niangming Duan; Zhibing Jiang; Jiang Shen; Haibo Jiang; Hailong Huang; Lingfeng Zhou; Dongping Shi; Mei Li; Ying Kang; Yuanhao Wang; Xubiao Yu (Environmental Research, 2026)

Precursor-engineered lignin-derived Co/N-doped carbon for high-efficiency electrocatalytic HMF oxidation: The critical role of pretreatment history - Chenxin Jin; Yajun Liu; Lingfeng Li; Yihan Wang; Changzhou Chen; Jianchun Jiang (Biomass and Bioenergy, 2026)

A hydrodynamics-assisted remote sensing method for estimating vertical distribution of total suspended matter in lakes: a case study of Poyang Lake - Hui Jiang; Jiawei Ouyang; Yao Liu; Lingfeng Wan; Yungen Sun (Journal of Hydrology, 2026)

Mechanisms of interlayer force transmission and slip surface penetration in pile-reinforced reservoir landslides with multi-sliding zones - Haojie Duan; Zongxing Zou; Yang Zhang; Lingfeng Wu; Jiang Li; Jianqiang Tao; Yikai Niu; Xinli Hu (Landslides, 2026)

Integrative multi-omics identifies CYP1B1 as a candidate molecular link between toxicant exposure and ferroptosis-related epithelial stress in COPD - Lingfeng Liu; Mingjun Jiang; Muzi Lei; Kun Du; Xiangyang Ye; Dafei Wei; Xiaowu Tan; Zhuang Mi; Yao Tang; Ruiting Sun; Sha Liu (Inflammation Research, 2026)

Nanoplastic exposure induces exoskeletal misdevelopment in juvenile Tachypleus tridentatus: Compensatory hardening versus molecular suppression - Lingfeng Jiang; Youji Wang; James Kar-Hei Fang; Khor Waiho; Wei Liu; Jae-Seong Lee; Xiaowan Ma; Menghong Hu (Marine Pollution Bulletin, 2026)

ATP-citrate lyase is a critical regulator of physiological and pathological angiogenesis - Chong Xu; Ying Lin; Zeyu Wang; Cailin Feng; Lingfeng Luo; Shuai Guo; Han Zhang; Lu Liu; Azhen Fan; Penglong Qi; Dongyang Jiang; Yiming Xu; et al. (Angiogenesis, 2026)

A novel transformer-based CO2 retrieval framework incorporating prior constraint and hierarchical features injection: assessment of transferability for Tansat-2 - Lingfeng Zhang; Lu Zhang; Xingying Zhang; Tiantao Cheng; Xifeng Cao; Tongwen Li; Dongdong Liu; Yang Zhang; Yuhan Jiang; Ruohua Hu; Haiyang Dou; Lin Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Polystyrene microplastics impede growth and induce behavioural toxicity in endangered juvenile horseshoe crabs (Tachypleus tridentatus) - Yi Jiang; Zhiyuan Yang; Lingfeng Jiang; Cheong-Meng Chong; Shanza Gul; Youji Wang; Khor Waiho; Xiaowan Ma; Zhi Chen; Menghong Hu (Marine Environmental Research, 2026)

Polyphthalocyanine-based nanostructure for sono-immunotherapy by reprogramming the tumor microenvironment and blocking immune checkpoint - Lingfeng Jiang; Jiawei Wang; Wenjun Liu; Xin Xie; Xiao Luo; Ling Tu; Liangqing Tang; Qing Zhang; Hongmei Yuan; Hanfeng Yang; Qi Li; Sujiao Cao; et al. (Chemical Engineering Journal, 2026)

Experimental and numerical study of a novel thin metal mesh infrared radiant burner - Jiarui Li; Tong Jiang; Lingfeng Dai; Hanlin Zhang; Chun Zou (Fuel, 2025)

Transcriptomic insights into an ancient and endangered species: Adverse effects of nanopolystyrene on the behavior and energy metabolism of Tachypleus tridentatus - Lingfeng Jiang; James Kar-Hei Fang; Youji Wang; Xiaowan Ma; Jae-Seong Lee; Menghong Hu (Journal of Hazardous Materials, 2025)

Temporal and spatial differentiation in the landslide sediment transfer potential in Wenchuan earthquake-impacted areas - Jiang Xiong; Huayong Chen; Chuan Tang; Ming Chen; Jiangang Chen; Tao Yang; Lingfeng Gong; Qingyun Shi; Xianzheng Zhang; Ning Li; Mingwei Li (Landslides, 2025)

Surface passivated 3D halide perovskite single crystal by 2D perovskite towards high performance soft X-ray detection and gamma-ray spectrum - Yan Xiong; Min Li; Shunsheng Yuan; Yuting Liu; Tong Jin; Jincong Pang; Sihao Xia; Mingquan Liao; Lingling Liu; Lingfeng Wu; Kuan Yew Cheong; Huayang Yu; et al. (Chemical Engineering Journal, 2025)

Risk prediction of catastrophic debris flows against the background of material changes and human engineering activity in the Wenchuan earthquake disturbance area - Jiang Xiong; Huayong Chen; Chuan Tang; Wanyu Zhao; Ming Chen; Tao Yang; Lingfeng Gong; Xianzheng Zhang; Qingyun Shi; Ning Li; Jiangang Chen (Bulletin of Engineering Geology and the Environment, 2025)

Preparation of SCOF/UiO-66-NH2 immobilized laccase biocatalytic membrane for micropollutants removal from water - Tiantian Wang; Lingfeng Zhao; Guanhua Liu; Xiaoyang Yue; Xiaobing Zheng; Li Ma; Yunting Liu; Mimi Chen; Yanjun Jiang (Chemical Engineering Journal, 2025)

Geomorphometric assessment of spatial transfer potential of landslides sediment in seismically impacted areas - Jiang Xiong; Huayong Chen; Chuan Tang; Chenxiao Tang; Lingfeng Gong; Ming Chen; Xianzheng Zhang; Tao Yang; Ning Li; Qingyun Shi; Mingwei Li (Natural Hazards, 2025)

DOPA Decarboxylase (DDC) in Pacific Oysters: Characterization and Role in Tyrosine Metabolism and Melanogenesis - Kunyin Jiang; Hong Yu; Lingfeng Kong; Shikai Liu; Shaojun Du; Qi Li (Marine Biotechnology, 2025)

A robust index was extracted to assess the prolonged changes in debris flow activity after a high magnitude earthquake - Jiang Xiong; Huayong Chen; Chuan Tang; Chenxiao Tang; Jiangang Chen; Tao Yang; Lingfeng Gong; Ming Chen; Qingyun Shi; Ning Li (CATENA, 2025)

Dynamic impact of hillslope landslide sediment transfer to ecological environment recovery in earthquake disturbed area - Jiang Xiong; Huayong Chen; Chuan Tang; Ming Chen; Tao Yang; Lingfeng Gong; Xianzheng Zhang; Qingyun Shi; Ning Li; Mingwei Li (Bulletin of Engineering Geology and the Environment, 2025)

Examination of the roles of CgTH in tyrosine metabolism and pigmentation of Pacific oyster (Crassostrea gigas) - Kunyin Jiang; Hong Yu; Lingfeng Kong; Shikai Liu; Shaojun Du; Qi Li (Aquaculture, 2025)

Abrupt enhanced Pacific warm water intrusion into the Sea of Okhotsk since the early Holocene - Xuguang Feng; Jianjun Zou; Xuefa Shi; Zhengquan Yao; Zhi Dong; Jiang Dong; Yonghua Wu; Ruxi Dou; Hualong Jin; Aimei Zhu; Xiaojing Wang; Qingchao Wang; et al. (Quaternary Science Reviews, 2024)

Mapping critical soil moisture thresholds of water stress for global grasslands - Lingfeng Shi; Yanlian Zhou; Wei He; Zhoutong Dong; Zhuoyou Jiang; Yuyan Wang; Yibo Liu; Weimin Ju; Zheng Duan (Journal of Hydrology, 2024)

The influence of digestive tract protein on cytotoxicity of polyvinyl chloride microplastics - Gonghao Liu; Qianwen Jiang; Lingfeng Qin; Zihang Zeng; Peng Zhang; Bo Feng; Xiaofeng Liu; Zhihe Qing; Taiping Qing (Science of The Total Environment, 2024)

High pre-tension reinforcing technology and design for ultra-shallow buried large-span urban tunnels - Qi Wang; Huayong Wei; Bei Jiang; Xuepeng Wang; Lingfeng Sun; Manchao He (International Journal of Rock Mechanics and Mining Sciences, 2024)

Catastrophic debris flow triggered by a June 26, 2023 rainstorm suggests the debris flow is still active 15 years after the Wenchuan seismic - Huayong Chen; Jiang Xiong; Wanyu Zhao; Jiangang Chen; Xianzheng Zhang; Hechun Ruan; Congxi Fang; Lingfeng Gong (Landslides, 2024)

Dynamic susceptibility assessment of debris flow hazard after a strong earthquake, Wenchuan County, Sichuan, China - Xianzheng Zhang; Chenxiao Tang; Yongbo Tie; Xiaojuan Li; Chuan Tang; Jiang Xiong; Ming Chen; Lingfeng Gong (Landslides, 2024)

Research and application of a tunnel active–passive cooperative control mechanism - Qi Wang; Lingfeng Sun; Bei Jiang; Zhongxin Xin; Yueru Guo (Tunnelling and Underground Space Technology, 2024)

Hypoxia impairs cellular energy allocation in the juvenile horseshoe crab Tachypleus tridentatus - Lingfeng Jiang; Meilian Huang; Chunhua Liu; Mohamed H. Abo-Raya; Xiaowan Ma; Youji Wang; Menghong Hu (Journal of Experimental Marine Biology and Ecology, 2024)

cAMP-Mediated CREM-MITF-TYR Axis Regulates Melanin Synthesis in Pacific Oysters - Kunyin Jiang; Hong Yu; Lingfeng Kong; Shikai Liu; Qi Li (Marine Biotechnology, 2024)

Impact of hypoxia on glucose metabolism and hypoxia signaling pathways in juvenile horseshoe crabs Tachypleus tridentatus - Lingfeng Jiang; Yueyong Shang; Yuntian Shi; Xiaowan Ma; Malik ShahZaib Khalid; Meilian Huang; James Kar-Hei Fang; Youji Wang; Kianann Tan; Menghong Hu (Marine Environmental Research, 2024)

Nanofiltration membrane with modified nano-gradient structure and positive charge for Li separation from high Mg/Li ratio brine - Peng Zhao; Fei Guo; Lingfeng Wang; Huange Zhen; Ning Zhang; Shaohua Yin; Guoli Zhou; Xuehua Ruan; Gaohong He; Xiaobin Jiang (Desalination, 2024)

Transcriptomic and Physiological Analysis Reveal Melanin Synthesis-Related Genes and Pathways in Pacific Oysters (Crassostrea gigas) - Kunyin Jiang; Chengxun Xu; Hong Yu; Lingfeng Kong; Shikai Liu; Qi Li (Marine Biotechnology, 2024)

Prediction of debris flow blocking river hazard chain by the numerical simulation: the Cutou catchment, Wenchuan County, China - Xianzheng Zhang; Yongbo Tie; Chenxiao Tang; Yajie Yu; Lingfeng Gong; Jiang Xiong (Bulletin of Engineering Geology and the Environment, 2024)

Genetic improvement of oysters: Current status, challenges, and prospects - Kunyin Jiang; Chen Chen; Gaowei Jiang; Yong Chi; Chengxun Xu; Lingfeng Kong; Hong Yu; Shikai Liu; Qi Li (Reviews in Aquaculture, 2024)
Oysters are one of the most commercially important shellfish species and have been cultured for thousands of years. Oyster aquaculture supports the major aquaculture industries in many countries. Over the last few decades, the oyster breeding and aquaculture industries have developed rapidly to meet the continually growing demand. Many researchers have made significant efforts toward the genetic improvement of commercially important traits in oysters. Some strains with fast‐growing, disease‐resistant, and stable shell‐colours have been developed through selective breeding. Some hybrid varieties have been developed by crossing different geographical populations or cultivated strains. Several hybrids exhibit considerable genetic variation and improved productive performance. Additionally, polyploid induction technologies have been applied in the oyster aquaculture industry, which provides a useful tool for performance improvement and genetic containment of cultured stocks. At present, the development of molecular breeding also provides a great opportunity for oyster genetic improvement. These advances in oyster breeding have improved the quality of oysters, brought great economic benefits, and been conducive to the sustainability of oyster production. Nonetheless, there are still some limitations and obstacles in oyster breeding, such as infectious diseases, summer mortality, conservation of germplasm resources, environmental contamination, and climate change. The present review provides an overview of the current status, challenges, and prospects in oyster breeding.

Saving the overlooked mangrove horseshoe crabs-A perspective from enhancing mangrove ecosystem conservation - Yuntian Shi; Shuhui Li; Yaowu Li; Lingfeng Jiang; Fahim Ullah Khan; Khor Waiho; Youji Wang; Menghong Hu (Marine Environmental Research, 2024)

Application of remote sensing monitoring to the spatiotemporal variation in debris flow activity in the catastrophic Wenchuan seismic area - Jiang Xiong; Huayong Chen; Chuan Tang; Ming Chen; Ming Chang; Xianzheng Zhang; Lingfeng Gong; Ning Li; Qingyun Shi; Mingwei Li (CATENA, 2023)

Mediation Effect of Body Mass Index on the Association of Urinary Nickel Exposure with Serum Lipid Profiles - Sibo Wang; Tiankai Shan; Jun Zhu; Qiqi Jiang; Lingfeng Gu; Jiateng Sun; Yulin Bao; Bo Deng; Hao Wang; Liansheng Wang (Biological Trace Element Research, 2023)

Transcriptome Analysis of Reciprocal Hybrids Between Crassostrea gigas and C. angulata Reveals the Potential Mechanisms Underlying Thermo-Resistant Heterosis - Gaowei Jiang; Yin Li; Geng Cheng; Kunyin Jiang; Jianmin Zhou; Chengxun Xu; Lingfeng Kong; Hong Yu; Shikai Liu; Qi Li (Marine Biotechnology, 2023)

Variability of rainfall time distributions and their impact on peak discharge in the Wenchuan County, China - Jiang Xiong; Chuan Tang; Lingfeng Gong; Ming Chen (Bulletin of Engineering Geology and the Environment, 2021)

Activity characteristics and enlightenment of the debris flow triggered by the rainstorm on 20 August 2019 in Wenchuan County, China - Jiang Xiong; Chuan Tang; Ming Chen; Xianzheng Zhang; Qingyun Shi; Lingfeng Gong (Bulletin of Engineering Geology and the Environment, 2021)

Seasonal and Spatial Variation of Pelagic Microbial Food Web Structure in a Semi-Enclosed Temperate Bay - Haibo Li; Xue Chen; Michel Denis; Yuan Zhao; Lingfeng Huang; Zengjie Jiang; Wuchang Zhang; Tian Xiao (Frontiers in Marine Science, 2020)

Expression and DNA methylation pattern of reproduction-related genes in partially fertile triploid Pacific oysters Crassostrea gigas - Qun Jiang; Qi Li; Hong Yu; Lingfeng Kong (Genes & Genomics, 2017)

QSAR modeling and in silico design of small-molecule inhibitors targeting the interaction between E3 ligase VHL and HIF-1 $$α $$ α - Jing Pan; Yanmin Zhang; Ting Ran; Anyang Xu; Xin Qiao; Lingfeng Yin; Weineng Zhou; Lu Zhu; Junnan Zhao; Tao Lu; Yadong Chen; Yulei Jiang (Molecular Diversity, 2017)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Inheritance and Variation of Genomic DNA Methylation in Diploid and Triploid Pacific Oyster (Crassostrea gigas) - Qun Jiang; Qi Li; Hong Yu; Lingfeng Kong (Marine Biotechnology, 2016)

Genome-Wide Analysis of Simple Sequence Repeats in Marine Animals—a Comparative Approach - Qun Jiang; Qi Li; Hong Yu; Lingfeng Kong (Marine Biotechnology, 2014)

Expanded Flap to Repair Facial Scar Left by Radiotherapy of Hemangioma - Donghong Zhao; Xinrong Ma; Jiang Li; Lingfeng Zhang; Baozhen Zhu (Cell Biochemistry and Biophysics, 2014)

Inhibitory effect of Salicornia europaea on the marine alga Skeletonema costatum - Dan Jiang; LingFeng Huang; YongQing Lin; LingLing Nie; SuLian Lv; TingYun Kuang; YinXin Li (Science China Life Sciences, 2012)

Identification and characterization of 43 microsatellite markers derived from expressed sequence tags of the sea cucumber (Apostichopus japonicus) - Qun Jiang; Qi Li; Hong Yu; Lingfeng Kong (Journal of Ocean University of China, 2011)